China's anti-corruption campaign, political connections and private firms' debt financing. Issue 4 (15th August 2019) - Hu, Yiming; Xu, Mingxia
Abstract : Purpose: The purpose of this paper is to shed light on the deleveraging impact of the anti-corruption campaign since the 18th National Congress of the Communist Party of China (CPC) on private firms with political connections, relative to those without political connections. Design/methodology/approach: In this paper, taking the anti-corruption campaign employed from the end of 2012 as an exogenous shock, the authors design a quasi-experiment difference-in-difference approach to examine how the loss and failure of political connections impacts private firms' debt financing. Findings: The authors find that the loss and failure of political connections following the anti-corruption campaign since the 18th CPC National Congress causes the yearly new debt ratios of treatment firms with political connections to decrease, relative to those of control firms without political connections. This outcome is more pronounced for provinces with more cadres excluded in the anti-corruption campaign since the 18th CPC National Congress, which rendered politically connected firms susceptible to lose connections with central or provincial cadres. To explore the mechanism, the authors find that following the anti-corruption campaign since the 18th CPC National Congress, politically connected firms limit rent-seeking activities, whereas resource acquisition is weakened. The authors also find that the impact of the anti-corruption campaign since the 18th CPC National Congress on the debt financing of politically connected firms, relative to their counterparts, is more pronounced for groups with high levels of information asymmetry and for less explicit guarantee groups. Finally, politically connected firms are more likely to be dominated by internal funds in dealing with a loss of advantages in debt financing, compared with their counterparts without political connections. Research limitations/implications: The findings in this study suggest that the loss or failure of previous political connections following Xi's anti-corruption campaign make politically connected firms lose the advantages in debt financing through the rent-seeking, resource acquisition, information asymmetry, implicit guarantee channels, which provide new evidence for research on the impact of the anti-corruption campaign since the 18th CPC National Congress on private firms' financing behaviors via the loss or failure of existing political connections. Practical implications: The findings in the study will have some inspiration for policy makers and entrepreneur. Originality/value: This study provides new evidence on the different impacts of Xi's anti-corruption campaign on private firm's debt financing between politically connected and unconnected firms.